PENGANGKATAN PJ KEPALA DAERAH PADA PEMILU SERENTAK 2024 DALAM PERSPEKTIF HUKUM DAN DEMOKRASI - Prayitno, Isnu Harjo; Pahlawan MP, HM Rezky (Rechtsregel : Jurnal Ilmu Hukum, 2024)
The General Election held on February 14, 2024 has elected the President and Vice President, Members of the DPR, Members of the DPRD and Members of the DPD. In 2024, Regional Head Elections were also held simultaneously throughout Indonesia, in which there were 271 regional governments filled by Acting Regional Heads both in Provinces, Regencies or Cities. The Acting Regional Heads who were appointed directly by the Central Government through the Ministry of Home Affairs are under the responsibility of the President. Many people doubt the independence of the Acting Regional Heads appointed by the Ministry of Home Affairs, especially when associated with the political interests of the current rulers, although legally it is considered not to violate existing laws and regulations. However, in terms of democracy, it is considered to harm the spirit of democracy which prioritizes people's sovereignty through the results of regional head elections rather than the results of appointments from the central government. The problems raised are: 1) How are the arrangements for the appointment of Acting Regional Heads based on a legal perspective?; 2) How is the appointment of 271 Acting Regional Heads ahead of the 2024 Simultaneous Elections based on a democratic perspective? This research is a normative legal research using a statute approach, a conceptual approach and a case approach. Normative legal research relies on secondary data derived from primary legal materials, secondary legal materials, and tertiary legal materials, so the data collection technique is to use documentary studies, namely studies that examine various documents, both those related to laws and regulations and existing documents. The research data is analyzed through qualitative legal analysis and the results are presented in a descriptive analytical manner